Analisis Permintaan Pangan Rumah Tangga Menurut Tingkat Ketahanan Pangan di Propinsi Jawa Tengah (Analisis Data Susenas 2008) - Yunastiti Purwaningsih; Slamet Hartono; Masyhuri Masyhuri; Jangkung Handoyo Mulyo (EKO-REGIONAL, 2010)
The phenomenon of rising food’s prices trend lead to lower of the purchasing power of society and so on have an impact on decreasing household’s demand for food. On the other hand, increase of food prices also have an impact toward household’s food accessibility, that household difficult to access food and the subsequent impact at household’s food security. Based on this phenomenon, hence this research estimates the demand of household’s food related to the level of food security in Central Java province. The source of data is the Panel of SUSENAS Consumption Module in March 2008 of the Central Bureau of Statistics, in the form of raw data. A systemic approach to the Almost Ideal Demand System (AIDS) in the form of linear approximation (LA/AIDS) was applied to analysis the data. The results of analysis show that all of the food commodities are non giffen goods, and is inelastic, except tobacco which is elastic as well as noodles for food-insecure households are unitary. Instant foods and beverages are the substitution food of rice for the food-secure, food-insecure, and food-vulnerable household, while at food-insecure households; noodles become the substitution food of rice. Most of the food commodities are the goods of daily needs, and tobacco is a luxury item. The recommended suggestions are the need of efforts to chase the total consume of tobacco, otherwise to reduce the total number of smokers, to control the quality and security of food in the food industry and to make innovation on producing noodles using local raw material (other than flour).                           Key words: household’s demand for food, Panel of SUSENAS, Almost Ideal Demand System